Cheese-rolling races - Waring, Rob; Heinle Cengage Learning (London : Heinle, Cengage Learning/National Geographic, 2008)
Many towns have special events. However, one town in England has a very unusual oe. At the start, someone pushes a piece of cheese down a hill. Then, the people run after the cheese
Title from title screen
Video and audio on DVD
Pre-intermediate 1000 headwords
DVD format
Optional audio and subtitle in American English or British English
Keywords: Geography